A Candidate Secreted Effector Protein of Rubber Tree Powdery Mildew Fungus Contributes to Infection by Regulating Plant ABA Biosynthesis - Li, Xiao; Liu, Yuhan; He, Qiguang; Li, Sipeng; Liu, Wenbo; Lin, Chunhua; Miao, Weiguo (Frontiers in Microbiology, 2020)
Powdery mildew widely infects crops and economic plants causing substantial losses. Rubber tree (Hevea brasiliensis) is the primary source of natural rubber, and powdery mildew infection causes significant losses to natural rubber yields. How the causal agent, Erysiphe quercicola establishes successful infection in rubber trees is largely unknown. Previously, 133 candidate secreted effector proteins (CSEPs) were identified in powdery mildew fungus. In this study, we characterize a CSEP named EqCSEP01276 for its function in suppressing host plant defense responses. We show that EqCSEP01276 is a secreted protein and able to disturb the localization of 9-cis-epoxycarotenoid dioxygenase 5 (HbNCED5), a key enzyme in abscisic acid (ABA) biosynthesis in plant cell chloroplasts of H. brasiliensis. We also show that this effector inhibits ABA biosynthesis, and that in H. brasiliensis ABA is a positive regulator of the plant immune response against powdery mildew. Our study reveals a strategy by which powdery mildew fungus manipulates plant ABA-mediated defense for a successful infection.